2014
DOI: 10.1159/000358867
|View full text |Cite
|
Sign up to set email alerts
|

The C in TORCH: A Cost-Effective Alternative to Screening Small-for-Gestational-Age Infants

Abstract: Background: Infants born with birth weights under the 10th percentile for their gestational age are classified as small for gestational age (SGA). TORCH infections are reported to be associated with SGA infants. With the low incidence of infections, screening is likely to be expensive and of low utility. Objective: The objective of this study was to determine the utility and cost-effectiveness of screening SGA infants with TORCH serology titers, urine cytomegalovirus (CMV) cultures and cranial ultrasounds. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…A Dutch study of TORCH screening in 112 SGA neonates found only 2 patients with evidence of congenital CMV infection. 11) In a study by Wei et al 9) of 117 SGA infants in whom TORCH titer testing was done, only two infants showed positive results (each positive for CMV IgM and HSV IgM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Dutch study of TORCH screening in 112 SGA neonates found only 2 patients with evidence of congenital CMV infection. 11) In a study by Wei et al 9) of 117 SGA infants in whom TORCH titer testing was done, only two infants showed positive results (each positive for CMV IgM and HSV IgM).…”
Section: Discussionmentioning
confidence: 99%
“…With low incidence of TORCH in the general population, screening is likely to be of low utility and high expense. Studies reviewing TORCH screening have reported very low incidences of positive findings: 3 out of 23 SGA neonates in a Canadian study, 7) 9 out of 117 SGA neonates in a USA study, 9) and 1 out of 75 SGA in another USA study. 8) In addition, SGA and IUGR rarely present as unique features of TORCH infection.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…La infección por CMV es una causa conocida de retardo en el crecimiento intrauterino secundario a la insuficiencia placentaria generada por la infección de las células trofoblásticas 97,98 (v. apartado «Fisiopatología de la infección en el feto»). El estudio de CMV en un RN PEG (menor que el percentil 10) sin otro síntoma es controversial 44,96,99 ; sin embargo, en el contexto de una búsqueda activa o un cribado selectivo de CMV en RN, Lorenzoni et al 100 estudiaron 504 RN prematuros o PEG graves (menor que el percentil 3) y encontraron un 3,7% de RN positivos para CMV. A su vez, en una experiencia nacional de cribado de CMV en RN hospitalizados se observó que el 3,3% de los PEG graves estudiados presentaron una infección congénita por CMV, sin hallar otra causa atribuible al bajo peso en un 40% de ellos 101 .…”
Section: Sospecha Clínica En El Recién Nacidounclassified
“…Além das causas congênitas, existem as causas adquiridas após o nascimento e podem ocorrer devido a medicamentos ototóxicos, infecção por meningite e infecções congênitas causadas por Toxoplasma gondii, Rubeolla vírus, Citomegalovírus e Herpes simplex vírus, conhecidas como TORCHS. Existem outras causas menos frequentes de origem adquirida, como traumatismo cranioencefálico e doenças que acometem a orelha, como a otosclerose, petrosite e outras (WEI et al, 2014;SIMÕES, 2017).…”
Section: Lista De Figurasunclassified